THE INFORMATION SOCIETY AND THE PARADIGM OF THE INFORMATION COMPONENT OF POLITICAL SECURITY - M. M. Abazalieva; E. A. Shabanova (Современная наука и инновации, 2022)
The transition of humanity from the stage of industrial society, where production played a leading role, to the information society of the post-industrial type, where the main role belongs to information, characterized our century as the "information age". Information exchange, information economy, digital cities, and in General the further development of electronic information technologies became a feature of civilizational development. Along with the above, humanity is increasingly concerned about the protection of personal data, the quality of security of critical nuclear and other strategically important facilities, the safety of information about state resources, etc. Consequently, the growth of threats from the information component of political security suggests that a new concept and system for ensuring state security is needed, which is closely related to information security in all its characteristics.